(untitled) (Lex Scientia Law Review, 2024)
The huge structural inequality in agrarian tenure in Indonesia after 78 years of independence, where a small elite controls the majority of land, contradicts the principles of egalitarianism and social justice enshrined in Indonesia’s agrarian constitutionalism. In this context, corruption in the agrarian sector, especially in the palm oil and forestry industries, shows weaknesses in monitoring and law enforcement. The Job Creation Law and other liberal-capitalistic policies are feared to potentially violate human rights, including the rights to land, work, and a healthy environment. Failure to implement agrarian reform has impacted food sovereignty, social injustice, and environmental damage. The neglect of human rights principles in agrarian issues, such as land grabbing and discrimination in access to natural resources, as well as the failure to provide effective conflict resolution mechanisms, has increased agrarian inequality and conflict. This research uses a normative juridical approach (library research), and the analysis is carried out using a statute approach, conceptual approach, comparative approach, historical approach, and futuristic approach. Research Results To achieve agrarian justice, serious efforts are needed, including restoring agrarian constitutionalism as the foundation of the nation’s life, forming an Agrarian Reform Advisory Board, revoking the Job Creation Law, forming an Agrarian Reform Implementing Agency directly under the President, and implementing priority locations for agrarian reform. It is also important to stop arrests, intimidation, and violence against farmers, indigenous peoples, laborers, fishermen, and activists by the police, and restore fuel subsidies for small farmers, traditional fishermen, and vulnerable communities. The role of people’s organizations and social movements in strengthening people’s initiative-based agrarian reform practices and calling for a holistic and social justice-focused approach to address agrarian issues in Indonesia.